2017
DOI: 10.1002/jez.2134
|View full text |Cite
|
Sign up to set email alerts
|

Chronic repeated exposure to weather‐related stimuli elicits few symptoms of chronic stress in captive molting and non‐molting European starlings (Sturnus vulgaris)

Abstract: Repeated exposure to acute stressors causes dramatic changes in an animal's stress physiology and the cumulative effects are often called chronic stress. Recently we showed that short-term exposure to weather-related stimuli, such as temperature change, artificial precipitation, and food restriction, cause acute responses in captive European starlings (Sturnus vulgaris). Here, we examined the effect of repeated exposure to weather-related stressors on heart rate and corticosterone (CORT) of captive non-molting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…In both studies, corticosterone levels decreased over time, potentially indicating that birds were habituating to housing conditions throughout the study. In study 1 there were no detectable effects on corticosterone, replicating earlier studies showing that songbirds can respond to storm cues without modulating glucocorticoid levels (Breuner et al, 2013;de Bruijn et al, 2017). In contrast, in study 2 we found lower corticosterone levels in birds exposed to inclement winter weather cues twice per week.…”
Section: Corticosteronesupporting
confidence: 87%
See 1 more Smart Citation
“…In both studies, corticosterone levels decreased over time, potentially indicating that birds were habituating to housing conditions throughout the study. In study 1 there were no detectable effects on corticosterone, replicating earlier studies showing that songbirds can respond to storm cues without modulating glucocorticoid levels (Breuner et al, 2013;de Bruijn et al, 2017). In contrast, in study 2 we found lower corticosterone levels in birds exposed to inclement winter weather cues twice per week.…”
Section: Corticosteronesupporting
confidence: 87%
“…This may represent a downregulation of the HPA axis under chronic stress conditions (de Bruijn et al, 2017). Indeed, the relationship between environmental stressors and baseline corticosterone levels is not as established as some studies suggest.…”
Section: Corticosteronementioning
confidence: 96%
“…It is possible that the ACTH response between the CRH/AVP and shearing challenges differed because the shearing challenge had to be psychologically perceived in order to activate the HPA-axis. The increase in ACTH responding to the shearing challenge, however, is a classic sign of down-regulation of the HPA-axis during chronic stress while maintaining responsivity to novel challenges [45, 4850]. This down regulation of the HPA-axis may be protective against the detrimental effects of long-term high levels of circulating glucocorticoids in chronically stressed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Birds exposed to two simulated storms per week may lower corticosterone levels to conserve energy. This may represent a downregulation of the HPA axis under chronic stress conditions (de Bruijn et al, 2017). Indeed, the relationship between environmental stressors and baseline corticosterone levels is not as established as some studies suggest.…”
Section: Corticosteronementioning
confidence: 96%